2020
DOI: 10.3389/fphar.2020.577062
|View full text |Cite
|
Sign up to set email alerts
|

α-Cyperone Confers Antidepressant-Like Effects in Mice via Neuroplasticity Enhancement by SIRT3/ROS Mediated NLRP3 Inflammasome Deactivation

Abstract: α-Cyperone (Cy) is a major active compound of Cyperus rotundus that has various pharmacological activities. But whether Cy possesses antidepressant effect is unknown. In this study, we exposed mice to chronic unpredictable mild stress (CUMS) with or without intervention with Cy. Our results showed that Cy significantly improved the depressive phenotypes in sucrose preference test, tail suspension test and forced swimming test. Meanwhile, increased SIRT3 expression, reduced ROS production and activated NF-κB si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 34 publications
0
15
1
Order By: Relevance
“…Collectively, these studies have demonstrated a positive feedback interaction between SIRT3 and PGC-1α, providing SIRT3/PGC-1α activation as a viable strategy for the intervention of DCM. Moreover, SIRT3 has been reported to be a crucial negative regulator of NLRP3 [40][41][42][43]. Mechanistically, SIRT3 deacetylates SOD2, leading to SOD2 activation, which impairs NLRP3 inflammasome assembly and activation [41].…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these studies have demonstrated a positive feedback interaction between SIRT3 and PGC-1α, providing SIRT3/PGC-1α activation as a viable strategy for the intervention of DCM. Moreover, SIRT3 has been reported to be a crucial negative regulator of NLRP3 [40][41][42][43]. Mechanistically, SIRT3 deacetylates SOD2, leading to SOD2 activation, which impairs NLRP3 inflammasome assembly and activation [41].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, most of the biological activities of the rhizomes of C. rotundus have been attributed to the sesquiterpenes [ 36 ]. It is reported that isocyperol and α-cyperone, known as major sesquiterpene components of the rhizomes of C. rotundus , have various pharmacological activities, such as anti-inflammation, antivirulence, antigenotoxic, antibacterial and anti-depressant effects [ 37 , 38 , 39 , 40 , 41 , 42 ]. For example, isocyperol and α-cyperone have an inhibitory effect on inflammation through suppression of the NF-κB pathway [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Saikosaponin, the main chemical component of Chaihu, has sedative, antipyretic, immune enhancement, anti-in ammatory, antiviral, liver, and antitumor effects. The α-germanone of Xiangfu has an antidepressant-like effect [31], and Jiawei Xiangfu Decoction combined with acupuncture can signi cantly improve the sleep state of menopausal insomnia patients with liver stagnation and qi stagnation [32]. The main active ingredients of Chuanxiong have both a sedative effect [26] and the potential to improve depression.…”
Section: Discussionmentioning
confidence: 99%